Level of Community Knowledge About Medicine for Adult Worms in Baru Village Siantar Utara District - Beta Haninditya (PT Inovasi Pratama Internasional, 2022)
Worm disease can cause problems because it causes loss of carbohydrates and protein as well as blood loss, thereby reducing the quality of human resources. The largest nematodes and infecting hundreds of millions of people are roundworms ( Ascaris lumbricoides ), whipworms ( Trichuris trichiura ), and hookworms ( Ancylostoma duodenale and Necatoramericanus ). These types of worms are widely found and easy to grow in tropical and subtropical Asia. And public awareness of the disease is still low. In particular, the new Kelurahan is one of the kelurahan located in Pemangsiantar, which is one of the kelurahan with a dense population, with various age levels. Therefore the authors measure the level of public knowledge of adult worm disease. From the results of the research that the author did using questionnaire data using respondent data with sample data as many as 30 respondents, it was found that the new urban village had a good level of knowledge about the disease, the data can be seen from testing data using the SPSS application with a level of correlation accuracy. the good one.